Direct Search for Dark Matter with DarkSide. (October 2015) - Agnes, P; Alexander, T; Alton, A; Arisaka, K; Back, H O; Baldin, B; Biery, K; Bonfini, G; Bossa, M; Brigatti, A; Brodsky, J; Budano, F; et al.
Abstract: The DarkSide experiment is designed for the direct detection of Dark Matter with a double phase liquid Argon TPC operating underground at Laboratori Nazionali del Gran Sasso . The TPC is placed inside a 30 tons liquid organic scintillator sphere, acting as a neutron veto, which is in turn installed inside a 1 kt water Cherenkov detector. The current detector is running since November 2013 with a 50 kg atmospheric Argon fill and we report here the first null results of a Dark Matter search for a (1422 ± 67) kg.d exposure. This result correspond to a 90% CL upper limit on the WIMP-nucleon cross section of 6.1 × 10 -44 cm 2 (for a WIMP mass of 100 GeV/c 2 ) and it's currently the most sensitive limit obtained with an Argon target.